The Effects of migratory seasonal farmwork on psychomotor development and growth among children ages 0-5 years in Southeastern Anatolia - Zeynep Simsek; Ibrahim Koruk (Turkish Journal of Public Health, 2011)
Objective:The aim of this cross-sectional survey is to investigate the role of migratory farmworker on childhood growth and psychomotor development. Method: We studied 174 children ages 0-5 years raised in migratory farmworker families (n=174), and compared them to a sample of non-farm workers’ children (n=174) selected by probability sampling method. Data were collected using a structured questionnaire and anthropometric measurements, and Ankara Developmental Screening Inventory. Results: Stunting was found in 43.1% of the farmworker’s children; 21.3% were in non-farmworker’s children. Farmworker mothers reported that none of their children had been monitored by healthcare professionals. Being from a migratory farmwork family (OR 2.6; 95% CI 1.4-4.7; p=0.001) and maternal education (OR 0.88; 95% CI = 0.78-0.99; p=0.040) were found to be factors associated with stunted growth after controlling for confounding factors such as economic situation, number of children, household size and maternal age. Conclusion: Children of migratory farmwokers represent a vulnerable population that deserves special attention in terms of healthcare rights and primary healthcare services. Key Words: Migratory farmwork, children, growth, development Güneydoğu Anadolu Bölgesi’nde 0-5 yaşları arasındaki çocukların büyüme ve psikomotor gelişimine mevsimlik tarım işçiliğinin etkisi Amaç: Kesitsel tipteki bu araştırmanın amacı, mevsimlik tarım işçiliğinin çocukların büyüme ve psikomotor gelişimine etkisini araştırmaktır. Yöntem: Olasılıklı örnekleme yöntemiyle seçilen 174 göçebe tarım işçisi ailenin çocuğu ve 174 tarım işçisi olmayan ailenin çocuğu büyüme ve gelişme açısından karşılaştırılmıştır. Veri toplamada soru formu, antropometrik ölçümler ve Ankara Gelişim Tarama Envanteri kullanılmıştır. Bulgular: Bodurluk tarım işçisi ailelerin çocuklarında %43.1, tarım işçisi olmayan ailelerin çocuklarında %21.3’dür. Mevsimlik tarım işçisi anneler çocuklarının büyüme ve gelişme izlemlerinin yapılmadığını bildirmişlerdir. Ekonomik durum, çocuk sayısı, hanehalkı büyüklüğü ve annenin yaşı kontrol edildiğinde, mevsimlik tarım işçisi ailenin çocuğu olma (OR 2.6; %95 GA 1.4-4.7; p=0.001) ve annenin öğrenim düzeyi (OR 0.88; 95% CI = 0.78-0.99; p=0.040) bodurluk için ilişkili faktörler olarak saptanmıştır. Sonuç: Hassas bir grup olan mevsimlik tarım işçisi ailelerin çocuklarının temel sağlık hizmetlerine ve sağlık haklarına erişimlerinin sağlanması için çaba harcanmalıdır. Anahtar Kelimeler: Göçebe tarım işi, çocuklar, büyüme, gelişme